Riveting Hammer Vibration and Nerve Damage - Zimmerman, Jordan (Proceedings of the Wisconsin Space Conference, 2016)
Hand Arm Vibration Syndrome (HAVS) is an occupational disease affecting 50% of riveting hammer operators after 10 years of work.1 Current international standards (ISO 5349) seeking to protect workers from occupational vibration are not effectively predicting HAVS onset.1–3 Scarce research has been done which investigates the long term effects of riveting hammer vibration exposure and nerve regeneration. The present study examines the effects of typical occupational vibrational exposure on cutaneous mechanosensory peripheral nerve populations (lanceolates) and as well as nerve bodies (dorsal root ganglion) that are responsible for nerve regeneration. A piezoelectric sensor-based data acquisition system is used rather than the traditional laser vibrometer. Although data analysis is not complete, current results show that the piezoelectric system is a viable means of vibrational analysis for both laboratory and workplace research. It records dominant kilohertz frequencies in the riveting hammer vibration signal which are currently overlooked by ISO 5349.